Perspectives on continuing education in Ecuador in times of Covid-19 - Dillon Pérez, Francisco Xavier (2023)
This reflection article aims to be a theoretical and practical reference in the analysis of trends in Continuing Education in Ecuador in times of Covid-19. The work methodology used was quantitative, descriptive, exploratory and explanatory, where INEC indicators and academic indicators of the professional training and continuing education processes issued by the Technical Secretariat of the National System of Professional Qualifications (SETEC) were taken as a reference framework. The main conclusion and reflection of the research process has made it possible to identify a paradigm shift in the professional education and training processes in the country, which should be adjusted to the development of digital skills and the opening of new online and virtual continuing education courses. That allow the user to optimize their time and improve their professional profile.